1979
DOI: 10.1017/s0074180900013322
|View full text |Cite
|
Sign up to set email alerts
|

Temperatures and radii of O stars

Abstract: Angular diameters have been estimated for 18 O and 142 B stars using absolute intermediate-band photometry in the near infrared and they have been combined with integrated fluxes to yield effective temperatures. The effective temperatures of the O stars lie in the range 30000 K to about 47000 K. For a given subtype, the luminosity class I stars have lower effective temperatures than the main-sequence stars by about 1000 K. The absorption-line spectral types of the supergiants of types O and B reflect electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Figs. 1 and 2 show the correlations between the values of Underhill et al (1979;UDPD) and ours (CM) for T eff anc * M V res P ective ly* Tne rms residual is 0.017 for log T e f f and 0.287 for M v .…”
Section: Multiple Linear Regressions Have Been Performed Between the mentioning
confidence: 76%
See 1 more Smart Citation
“…Figs. 1 and 2 show the correlations between the values of Underhill et al (1979;UDPD) and ours (CM) for T eff anc * M V res P ective ly* Tne rms residual is 0.017 for log T e f f and 0.287 for M v .…”
Section: Multiple Linear Regressions Have Been Performed Between the mentioning
confidence: 76%
“…We begin with B type stars as there is an excellent paper of Underhill et al (1979) which evaluates many physical quantities for 160 0-B type stars which are among the stars observed in the 13 color system. The present paper describes the procedure we adopted to get preliminary relations for deriving T e ff's and My's.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic studies of a sample of stars have been carried out, e.g. by Underhill et al (1979), Bohm-Vitense (1981), and Malagnini et al (1982. Generally, these authors have demonstrated that Kurucz's models reproduce the observed visual distribution fairly well, while the UV flux is reproduced somewhat worse, but still satisfactorily.…”
Section: Lte Modelsmentioning
confidence: 99%
“…Work is still hampered by uncertainty in the exact shape of the interstellar extinction curve, (Seaton, 1979) and uncertainties in the stellar model atmospheres (Kurucz, 1979). Underhill et al (1979) have conducted a careful survey of hot star continuum intensity data, and derived temperatures and luminosities. Their findings indicate a lower temperature for higher luminosity stars of a given spectral type, in general agreement with earlier indications (e.g.…”
Section: Masses and Luminositiesmentioning
confidence: 99%